HUBUNGAN SELF MANAGEMENT DENGAN TINGKAT NYERI EPIGASTRIUM PADA MAHASISWA YANG MENGALAMI GASTRITIS (STIKES Telogorejo Semarang, 2024)
Background: Gastritis is an inflammation of the gastric mucosa that is acute and chronic. Gastritis disease often occurs in adolescents. Students often spend their activities with dense lecture activities, quite a lot of assignments and never think about their health, which makes them vulnerable to gastritis. Indications that occur in gastritis, namely pain in the epigastric area, one way to deal with pain is using self - management. Self-management is able to help someone in developing abilities and managing themselves. Purpose: This study aims to determine the relationship between self-management and the level of epigastric pain in students who have gastritis. Method: The design of this study used a quantitative method with a total sample of 70 respondents with a sampling technique using total sampling. The statistical test used is the Spearman rank correlation test. Research Results: The results of this study showed that the relationship between self-management and the level of epigastric pain in students who experienced gastritis obtained a p value of 0.553 (> 0.05) with a correlation coefficient of -0.072. So from the results of this study it was concluded that there was no significant relationship between self-management and the level of epigastric pain in students who experienced gastritis. Several self-management factors for gastritis are factors that include age, gender, student knowledge of various intrinsic and extrinsic factors so that self-management of Telogorejo STIKES Semarang students is known by researchers to be in the category of poor self-management and the level of epigastric pain the majority of students experience mild pain and moderate pain. Suggestion: It is hoped that students will pay attention to and improve their self- management knowledge properly so that they can suppress the recurrence of gastritis.